THE CHEMICAL COMPOSITION OF SOME SORGHUM GENOTIPES FOR GRAINS CULTIVATED IN THE CENTER OF MOLDOVA - SIMONA – FLORINA ISTICIOAIA; OANA MIRZAN; DIANA POPA; MARGARETA NAIE; VALENTIN VLADUȚ; IULIAN VOICEA (Journal of Engineering Studies and Research)
In the lab, three sorghum hybrids for grains cultivated in the Center of Moldova were analyzed qualitatively, two of them having white grains, and one having red grains. Two of the hybrids, one with white grains (Albanus) and one with red grains (Alize) came from Euralis SAS France, and the third, with white grains, came from N.A.R.D.I. Fundulea Romania (Fundulea 32). The results obtained from the laboratory investigations indicated that the variation of the chemical composition of the sorghum grain depending on the cultivated hybrid.